Development of Class D Inverter for Acoustics Energy Transfer Implantable Devices - Siti Huzaimah Husin; Mohd Shakir Md Saat; Yusmarnita Yusop; Zamre Abdul Ghani; Sing Kiong Nguang (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The working principle of half-bridde Class D Parallel-Resonant Inverter (PRI) as power amplifier is presented in this paper. Simulation of the model is carried out using Proteus.  In order to verify the simulation results, an experimental verification is done. This inverter is used to excite the PZT transducers at the suggested resonant frequency of 416 kHz with power level transferred through Acoustics Energy Transfer (AET) concept at about 80mW. As experimental outcome result, the system managed to transfer energy at 66mW to the receiver side.